(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article provides information about the ethnic composition of the Turkic Khaganate, which played a significant role in the lives of Central Asian peoples during the early Middle Ages. Sources and literature related to the issue under consideration are thoroughly analyzed. By analyzing these sources and literature, the author sheds light on the origin (ethnogenesis) and ethnic characteristics of numerous Turkic-speaking ethnic groups who lived within the territory of this political union.